Challenges for Latin American cities: Improving diagnosis or the need to shift the understanding urban inequality from fixed enclaves to mobile gradients - Paola Jirón (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Current urban interventions, particularly in cities in developing countries like Santiago de Chile, evidence major neglect in understanding the way contemporary living takes place and how it is changing under processes of globalization, global warming, technological advances, as well as specific national and local processes. Traditional ways of analysing urban living are no longer adequate to tackle urban issues, thus new questions need to be asked in order to achieve better comprehension.
Keywords: O18; O54; N96; Z19; 330; urban inequality; cities; Latin America